Detection of canine distemper virus (CDV) neutralising antibodies in small ruminants during peste-des-petits-ruminants virus (PPRV) surveillance in Zambia - Sara Lysholm; Nicola Logan; Johanna F Lindahl; Mikael Berg; Elin Johansson; Pernilla Karlsson Bergkvist; George Dautu; Ricky Chazya; Brian J. Willett; Musso Munyeme; Jonas Johansson Wensman (BMC Veterinary Research)
Abstract Canine distemper virus (CDV) is endemic in Zambia, while peste-des-petits-ruminants virus (PPRV) has not been detected. This study screened 962 farmed goats and 237 small ruminants at informal markets for PPRV antibodies using c-ELISA. A subset (n = 29) was re-analysed with virus neutralisation assays (VNA) for antibodies to PPRV and CDV due to cross-reactivity concerns. c-ELISA indicated 6.44% PPRV seroprevalence on farms and 3.80% at markets. While VNA detected no PPRV antibodies, 45% (13/29) tested positive for CDV, possibly suggesting cross-reactivity. Given the study’s limitations, further research is needed to determine whether PPRV is present in Zambia and assess potential cross-reactivity.